Development of a long-term fetal heart rate recorder using an ambulatory approach - Firoz Ahmed,; Zahari Mohamed,; Darus Mohd Alauddin Mohd Ali, (1999)
Ambulatory recorders have been widely used in the acquisition of adult electrocardiogram (ECG). Such an ambulatory system will also be beneficial for the recording of both the fetal and maternal ECG from the abdomen of pregnant women. This paper describes a device with the possibility of producing a fetal and maternal heart rate recorder system employing an ambulatory approach by using three electrodes for recording the abdominal signal. The signal is amplified and digitized by an amplifier and an analog to digital converter. The digitized signal is stored into static RAM (SRAM) and then downloaded to a personal computer (PC) through a serial interface circuit. Both the fetal and maternal heart rates can be measured from the downloaded signal. This paper also presents real data acquired by the constructed ambulatory recorder. The performance of the constructed recorder was found to be acceptable acquiring signal with system noise kept below 3mV peak to peak. Such signals are suitable for the measurement and analysis of both fetal and maternal heart rates